2021
DOI: 10.1038/s41598-021-98087-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota composition and intestinal integrity remain unaltered after the inclusion of hydrolysed Nannochloropsis gaditana in Sparus aurata diet

Abstract: The use of lysed microalgae in the diet of carnivorous fish can increase the bioavailability of proteins and bioactive compounds, such as unsaturated fatty acids or vitamins in the digestive tract. These are essential molecules for the proper physiological development of fish in aquaculture. However, some antinutritional components and other undesirable molecules can be released from an excess of microalgae supplied, compromising the integrity of the intestine. The inclusion of small amounts of hydrolized micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…In our results the diet containing M. gaditana (MI) showed a decrease in the values of all alpha diversity indices, compared to the control (FO), but not statistically significant. Cerezo-Ortega et al (2021) also reported no statistically significant differences in microbial diversity indices (alpha and beta diversity) in Sparus aurata gut after the inclusion of 5% hydrolysed M. gaditana .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our results the diet containing M. gaditana (MI) showed a decrease in the values of all alpha diversity indices, compared to the control (FO), but not statistically significant. Cerezo-Ortega et al (2021) also reported no statistically significant differences in microbial diversity indices (alpha and beta diversity) in Sparus aurata gut after the inclusion of 5% hydrolysed M. gaditana .…”
Section: Discussionmentioning
confidence: 91%
“…However, the above combination along with dietary inulin and the utilization of its b-glycans, has demonstrated immunostimulant effects, influencing intestinal gene expression (Cerezuela et al 2013; Reis et al 2021; Teixeira et al 2022). The use of M. gaditana showed that gut microbiota composition and intestinal integrity remained unaltered (Cerezo-Ortega et al 2021) or an increase in intestinal microbiota richness without affecting intestinal morphology and function (Jorge et al 2019). When used in combination with other species ( Chlorella sp., Arthrospira sp., Tisochrysis lutea , Scenedesmus almeriensis ) it was shown to favour the presence of probiotic bacteria in the gut and reduce the presence of pathogenic species (Garcia-Márquez et al 2023; Garcia-Márquez et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing number of reports that indicate the effects of microalgae consumption on gut microbiome with no adverse or positive effects on intestinal health in fish, [41,92] human trials, or animal models. [19] In our study, the microbiome composition was altered in fish receiving diets supplemented with Ns nutrient-replete L. incisa P127; the increase in Cetobacteria paralleled the increase in the inclusion level.…”
Section: Dietary Supplementation With Non-starved Biomass Alters Gut ...mentioning
confidence: 99%
“…89,90 In a first effort to explore the immunostimulatory activity of N. gaditana, Cerezuela the weight and length of S. aurata 91 ; however, its dietary inclusion did not affect parameters of the intestinal health and digestive capacity of S. aurata, but could modulate intestinal microbiota. 65,92 Recently, the ability of the genus Nannochloropsis to reduce the effects of different types of stress related to aquaculture has been explored. On the one hand, Monteiro et al 93 showed that Tackle Meagre (Argyrosomus regius) supplemented with N. gaditana at 1% and subjected to acute handling stress had lower gene expression of proinflammatory cytokines tnf-α and il-1β genes, as well as a lower number of parameters related to oxidative stress.…”
Section: Nannochloropsis Gaditanamentioning
confidence: 99%
“…Additionally, the expression of the β‐defensin ( bdef ) gene in HK leukocytes upregulated in the highest dose of microalgae at Week 4. Subsequent trials showed that the supplementation of N. gaditana at various concentrations improved the weight and length of S. aurata 91 ; however, its dietary inclusion did not affect parameters of the intestinal health and digestive capacity of S. aurata , but could modulate intestinal microbiota 65,92 …”
Section: Immunomodulatory Effects Of Dietary Microalgae In Fishmentioning
confidence: 99%